EVALUASI KOMPONEN GIZI PADA PAKAN UDANG FERMENTASI - Rahmania Rahman; Lahming Lahming; Ratnawaty Fadilah (Universitas Negeri Makassar, 2018)
This research aim is to know the description of nutrition quality from fermented shrimp feed that has been formulated. This research is divided into two stages. The first stage was the manufacture of flour which continues by analysis of protein levels, fat content, crude fiber levels, carbohydrate levels, moisture content and ash content and the second stage is the manufacture of fermentation shrimp feed. The type of this research is experiment using T test to compare treatment addition of mujair fish and addition of golden snail which is processed by using SPSS version 22. The parameters observed in fermentation shrimp feed include protein levels, fat content, crude fiber content, carbohydrate levels, moisture content and ash content. Based on the results of the best treatment research, it was obtained by addition of mujair fish with protein levels 20,8%, fat content 8,82%, crude fiber content 10,79%, carbohydrate content 45,94%, water content 3,65% and ash content 10,12 %.